Encyclopedia of Tudor England - Wagner, J. A. (John A.); Schmid, Susan Walters (ABC-CLIO, 2012)
This encyclopedia spans the period from the accession of Henry VII in 1485 to the death of Elizabeth I in 1603. It also examines pre-Tudor people and topics that shaped the Tudor period, as well as individuals and events whose influence extended into the Jacobean period after 1603.